Penerapan Mechanics Dynamics Aesthetics Framework pada Game Pengenalan Wisata Kota Malang - Muhamad Rizky Prahesa Putra; Eriq Muh. Adams Jonemaro; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Malang City is one of the most potential city for tourism destination in Indonesia. Therefore, it's nessescarry for Malang to have varios promotional media for tourism. In effort to invite the tourists to visit Malang city requires variety of media campaigns and one of the alternative media is a media campaign games form. Malang City Tour game is one kind of that media which take form as game. Through this game, player can get information about tourism destination, tour budget, as well as common knowledge about Malang by taking quiz. Malang City Tour is created by applying MDA Framework. This framework consist of mechanic which is rules and algorithm made by game designer to build the game. If mechanics work well, it'll build a dynamics, which is interaction between mechanics and player. This dynamics then automatically created aesthethics of player's responeses to dynamics. This game then tested using playtesting. Result shows that this game is well-functioned and has reached it aim whis is giving useful information about Malang's tourism to the player.